The Comparison Schema in the Successful Addiction, Unsuccessful Addiction and Non-Addiction Popular - Anisi Khoshlahjeh; Khadejeh Abolmaali; Zahra Khoshlahjeh; Hasan Alizadeh, F; Ehsan Imani (Drug Control Headquarters, Research and Education Office, 2010)
Objective: The purpose of this research was to compere schema in the successful addiction, unsuccessful addiction and non-addiction popular. Method: The method of the research the sample population in this study includes institutes f Birth again charity institutions in 1389. The variables like education (degree of high school), gender (only man) and age (25- ....) were controlled in three groups. The statistical sample consisted those 90 individuals who were tested by from GHQ and selected through the accessibility sampling. They based on relapse in 6 months assigned in the three groups, that successful addiction (non-relapse in 6 months), unsuccessful addiction (relapse in 6 months) and non-addiction popular. The practitioners completed test of "YSQ". After gathering in information, the data was deductively and descriptively analyzed. Results: For analyzing of data were applied statistical tests of ANCOVA. Conclusion: The results indicated that there is a significant difference between the three groups and the schema in the successful addiction, unsuccessful addiction and non-addiction popular (in 0.5 meaningful levels) can have a significant effect on the addiction (addiction to narcotic substances such as Crack).